Surveillance colonoscopy for colitis‐associated dysplasia and cancer in ulcerative colitis patients. Issue 3 (26th July 2015) - Hata, Keisuke; Kishikawa, Junko; Anzai, Hiroyuki; Shinagawa, Takahide; Kazama, Shinsuke; Ishii, Hiroaki; Nozawa, Hiroaki; Kawai, Kazushige; Kiyomatsu, Tomomichi; Tanaka, Junichiro; Tanaka, Toshiaki; Nishikawa, Takeshi; et al.
Abstract : Long‐standing ulcerative colitis patients are known to be at high risk for the development of colorectal cancer. Therefore, surveillance colonoscopy has been recommended for these patients. Because colitis‐associated colorectal cancer may be difficult to identify even by colonoscopy, a random biopsy method has been recommended. However, the procedure of carrying out a random biopsy is tedious and its effectiveness has also not yet been demonstrated. Instead, targeted biopsy with chromoendoscopy has gained popularity in European and Asian countries. Chromoendoscopy is generally considered to be an effective tool for ulcerative colitis surveillance and is recommended in the guidelines of the British Society of Gastroenterology and the European Crohn's and Colitis Organisation. Although image‐enhanced endoscopy, such as narrow‐band imaging and autofluorescence imaging, has been investigated as a potential ulcerative colitis surveillance tool, it is not routinely applied for ulcerative colitis surveillance in its present form. The appropriate intervals of surveillance colonoscopy have yet to be determined. Although the Japanese and American guidelines recommend annual or biannual colonoscopy, the British Society of Gastroenterology and the European Crohn's and Colitis Organisation stratified their guidelines according to the risks of colorectal cancer. A randomized controlled trial comparing random and targeted biopsy methods has been conducted in Japan and although the final analysis is still ongoing, the results of this study should address this issue. In the present review, we focus on the current detection methods and characterization of dysplasia/cancer and discuss the appropriate intervals of colonoscopy according to the stratified risks.